A call to collect and analyse recordings of personal independence payment assessments. Issue 5 (28th May 2022) - Webb, Joseph; Albert, Saul
Abstract: Recent UK policy changes enable claimants to record their Personal Independence Payment (PIP) assessments, presenting an opportunity to study how they are produced interactionally. Disabled people have often reported feeling disempowered by PIP assessments, and these assessments are notoriously inaccurate – the vast majority are overturned in the claimants' favour upon appeal. Given the quality of claimants' lives often depends on their outcome, it is urgent to learn how the assessment process yields so many successful appeals. Here we analyse a small sample of one PIP assessment recording, uploaded to YouTube by the claimant, to show the importance of understanding these high-stakes interactional situations. We intend for this to show the importance of looking at the interactional detail of PIP assessments, which have hitherto been hidden from scrutiny because of the difficulty of obtaining recordings of assessments.